Metformin - its anti-cancer effects in hematologic malignancies - Monika Podhorecka (Oncology Reviews, 2021)
The main anti-diabetic effect of metformin mediated through stimulation of adenosine monophosphate (AMP)-activated protein kinase (AMPK) is the inhibition of hepatic gluconeogenesis and triggering glucose uptake in skeletal muscles. Additionally, some new pathways, besides the AMPK activation, were discovered, that can explain wide-range properties of metformin. All these properties are now attracting the attention of researchers in the fields other than diabetes and the drug has been reported to have anti-cancer, immunoregulatory and anti-aging effects. Among others, the beneficial effects of metformin in hematological disorders like leukemias, lymphomas, and multiple myeloma were reported. Despite a great progress in therapy, these diseases are still incurable in most cases. Thus, there is an urgent need to discover novel, less toxic and more effective drugs especially for older or chemotherapy-resistant patients. In this review article, the current findings on the anti-cancer effect of metformin together with underlying possible mechanisms in blood cancers are discussed. However. to evaluate precisely these promising effects of metformin, more studies are required, because many of the published results are preclinical.